La poésie lyrique, un outil d’unification linguistique et politique - Anne-Marie Le Baillif (Interlitteraria)
Lyric poetry as a tool to unify language and politics points of view. We propose to examine how lyric poetry was used as a politic tool by French kings of the Renaissance period (1515–1589). In France, the building of a specific identity starts with François I Ordonnance de Villers-Cotterêts (1539): all official documents previously in Latin, had now to be in French. The second act was Defence et Illustration de la langue française published by Joachim du Bellay in 1549 ruling on the use of vernacular language in lyrical poetry. Both events gave impetus to the unification of the language, not only in official documents but also in everyday life. As each province had its own idioms, the proposal was ambitious.